Energy and nutrient recovery for municipal wastewater treatment: How to design a feasible plant layout?. (June 2015) - Khiewwijit, Rungnapha; Temmink, Hardy; Rijnaarts, Huub; Keesman, Karel J.
Abstract: Activated sludge systems are commonly used for robust and efficient treatment of municipal wastewater. However, these systems cannot achieve their maximum potential to recover valuable resources from wastewater. This study demonstrates a procedure to design a feasible novel configuration for maximizing energy and nutrient recovery. A simulation model was developed based on literature data and recent experimental research using steady-state energy and mass balances with conversions. The analysis showed that in the Netherlands, proposed configuration consists of four technologies: bioflocculation, cold partial nitritation/Anammox, P recovery, and anaerobic digestion. Results indicate the possibility to increase net energy yield up to 0.24 kWh/m 3 of wastewater, while reducing carbon emissions by 35%. Moreover, sensitivity analysis points out the dominant influence of wastewater organic matter on energy production and consumption. This study provides a good starting point for the design of promising layouts that will improve sustainability of municipal wastewater management in the future. Highlights: We demonstrate a five-step procedure to develop future sewage treatment plants. Steady-state energy and mass balances with conversions help to select scenarios. A promising scenario to treat and recover resources is proposed for Dutch case. Model shows recovery of energy yield of 0.24 kWh/m 3 or 39% of organic carbon load.